Neo Automatic Code to Improve Quality of Cardiopulmonary Resuscitation (CPR) in Society - Darmawan, Rendi Editya; Satino, Satino (Poltekkes Kemenkes Surakarta, 2024)
Background: The quality of cardiopulmonary resuscitation (CPR) in Indonesian society is poor. One solution is to give society a metronome called the Neo Automatic Code (NAC) to guide CPR when cardiac arrest patients are present. This study aims to analyze the effect of NAC on the compression depth and compression rate during CPR. Methods: A quick experimental study with a control group design, where the population is chosen by simple random sampling to distinguish between odd and even. The population is health cadres and youth with an age range of 16-56 years. The intervention group gets training 2 times to do CPR with Neo Automatic Code, and the control group gets training in CPR using standard procedure. We use a CPR manikin to measure variables. Data analyzed used Mann Whitney. Results: The Mann-Whitney test shows p = 0.001, concluding that there is a difference in the accuracy of depth and compression speed in CPR between the intervention and control groups. This means the NAC metronome can improve CPR performance in compression depth and compression rate. CPR uses a neo-automatic code metronome to ensure the user breathes regularly and helps the rescuer to constantly give compression. Conclusion: Neo automatic code can improve the quality of CPR in Indonesian society. A study about how many times training must be given to society, considering age, level of education, and kinds of jobs, is needed.